ResolvinD1 attenuates high-mobility group box 1-induced epithelial-to-mesenchymal transition in nasopharyngeal carcinoma cells - Yang, Pingli (Exp Biol Med (Maywood), 2019)
Epithelial-to-mesenchymal transition (EMT) process is prevalent during the progression of tumors. Nasopharyngeal carcinoma (NPC) is no exception. High-mobility group box 1 (HMGB1) was reported to have the effect of inducing EMT in malignancy. However, the impact of HMGB1-induced EMT in NPC is unclear. Resolvin D1 (RvD1) was reported to regress the progression of inflammation and apoptosis of phagocytes. The effect of RvD1 in the EMT is largely unknown. The current research explored the role of RvD1 on HMGB1-induced EMT in NPC. EMT markers were investigated in 10 NPC and 10 nasopharyngitis (NPG) patients using immunohistochemistry and Western blot. In vitro, expression of EMT markers and HMGB1 in CNE1 and CNE2 cells was assessed with immunohistochemical, Western blot, and confocal microscopy after treatment with recombinant human HMGB1 (rhHMGB1) or HMGB1 gene silencing or RvD1. The invasion and migration of NPC cells were detected by scratch test and transwell assay. Overexpression and gene silencing of lipoxin A4 receptor/formyl peptide receptor 2 (ALX/FPR2) and G protein-coupled receptor 32 (GPR32) in CNE2 cells confirmed the effect of RvD1 using Western blots. N-cadherin, vimentin, and HMGB1 were found up-regulated in NPC samples compared with NPG samples, while ZO-1 and E-cadherin were down-regulated in NPC tissues. RhHMGB1-induced EMT in CNE1 and CNE2 cells in a dose-dependent way. CNE2 cell lines treated with rhHMGB1 possessed greater invasion and migration ability, which was confirmed by gene silencing. RvD1 suppressed HMGB1-induced EMT in NPC cells via ALX/FPR2 and GPR32 receptors. These results showed that EMT was obvious in NPC. HMGB1 played a key role in inducing EMT. RvD1 inhibited HMGB1-induced EMT and might have potential application in the area of NPC treatment. IMPACT STATEMENT: Nasopharyngeal carcinoma has a high incidence in China. Discussing the molecular mechanism of nasopharyngeal carcinoma is important because of high recurrent rate and low quality of life after treatment. HMGB1, as an important inflammatory factor, promotes the process in many cancers. But little is known about how HMGB1 affects the progress of nasopharyngeal carcinoma cells. In our research, we assessed the role of HMGB1 on metastasis and invasion of nasopharyngeal carcinoma cells. The result of study indicates HMGB1-induced EMT in nasopharyngeal carcinoma cells. Furthermore, we observed that RvD1, which plays an actively protective role in many diseases, controls the migration and invasion of nasopharyngeal carcinoma cells by inhibiting the HMGB1-induced EMT. RvD1 can be further studied as a protective factor for nasopharyngeal carcinoma.